A descriptive review of the thermal transport mechanisms in mono and hybrid nanofluid-filled heat pipes and current developments. (1st June 2022) - Pandey, Harshit; Kumar Gupta, Naveen
Abstract: Heat pipes are phase change-based passive heat transfer devices currently being used across a wide range of applications. The mono and hybrid nanofluids are advanced heat transfer fluids that have huge potential to augment the thermal performance of the heat pipes. This review paper emphasizes the enhancement achieved in the thermal performance of the heat pipes using mono and hybrid nanofluid as working fluids. The current study is of great importance since it summarizes the results of the studies reported on mono and hybrid nanofluid-based heat pipes in last five years. In the current study, thermal transport mechanisms responsible for the change in thermal performance of heat pipes using nanofluids are identified. The identified thermal transport mechanisms have been analysed extensively and novel inter-relations are discussed. The current study also summarizes different operating and design parameters that have been found to influence the thermal performance of the heat pipes. The present work is beyond the current state of the art and contributes in further understanding of the nanofluid filled heat pipe technology.